2020
DOI: 10.1088/2631-7990/ab7b00
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser scanning strategies on selective laser melting of pure tungsten

Abstract: Three types of scanning strategies, including the chessboard scanning strategy, the zigzag scanning strategy and the remelting scanning strategy, were conducted to study the effects of scanning strategies on surface morphology, microstructure, mechanical properties and the grain orientation of selective laser melted pure tungsten. The results showed that the pores and cracks were main defects in SLM-processed tungsten parts. The pores could be eliminated using the remelting scanning strategy. However, the crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Since the liquid vortex can exert an ultra-high pressure to the side walls of the formed structures, it may induce severe cracks to a brittle material such as tungsten (W). Previous reports have shown that metal W can be easily cracked upon the impact of laser pulses when the pressure exceeds its tensile stress limit 77,78 . To investigate whether the liquid vortexes can cause cracks to the microstructures, we checked the ablated W sample we have prepared for antireflective studies 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the liquid vortex can exert an ultra-high pressure to the side walls of the formed structures, it may induce severe cracks to a brittle material such as tungsten (W). Previous reports have shown that metal W can be easily cracked upon the impact of laser pulses when the pressure exceeds its tensile stress limit 77,78 . To investigate whether the liquid vortexes can cause cracks to the microstructures, we checked the ablated W sample we have prepared for antireflective studies 51 .…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, both the thermal diffusivity and thermal conductivity of W are much higher than those of Ta, indicating that W should tend to cool more rapidly than Ta after laser heating. Additionally, the melting temperature of 3422 • C for W is relatively higher than that of 3017 • C for Ta [65,68]. For Ta, the smaller thermal conductivity and thermal diffusivity with a lower melting temperature must endow a relatively longer melting period than W so as to enable the interaction with surrounding oxygen species during fs-LAL.…”
Section: D Morphology Characterizationmentioning
confidence: 99%
“…They showed that with the same build, a long bidirectional scan strategy on one layer with 90-degree scan direction between layers led to least amount of residual stress. Guo et al [ 31 ] investigated the effect of scan strategy on surface quality, microstructure, and mechanical properties of the SLM build pure tungsten parts. They found that scan strategy significantly changed the surface morphology as well as the compressive stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was not a model built to address the scan direction rotation between layers in SLM. Considering the importance of the rotation angle to the various aspects [ 28 , 29 , 30 , 31 , 32 ] of the build, it is important to include it into the analytical model. This paper proposes an analytical thermal model for SLM that considers the scan direction rotation between layers.…”
Section: Introductionmentioning
confidence: 99%